2018
DOI: 10.5016/geociencias.v37i4.12274
|View full text |Cite
|
Sign up to set email alerts
|

Contaminação Por Nitrogênio E Fósforo De Águas Destinadas Ao Consumo Humano Em Região Com Intensa Atividade Suinícola

Abstract: A atividade suinícola na Região Sul do Brasil, é desenvolvida em pequenas propriedades, com passivo ambiental relacionados aos dejetos. Nesse sentido, a aplicação de dejetos em áreas agricultáveis, é uma prática comum com riscos potenciais de contaminação, para o solo e a água. Nesse sentido, o objetivo do presente trabalho é avaliar a contaminação por nitrogênio e fósforo de fontes de água destinadas ao consumo humano em região com intensa atividade suinícola no estado de Santa Catarina. Para isso, foram real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…These measures prevent or delay nutrients accumulation in soil and its losses, whether through volatilization (NH 3 ), percolation, or runoff. The absence of measures and monitoring of applications can compromise the quality of water resources present in the swine units, as observed by the studies by Cadoná et al [23] and Loss et al [41]. In the first study, these authors observed in the supply wells of four swine units located in Braço do Norte, SC, an increase in N and P concentrations of in the water.…”
Section: Use Of Swine Manure In Agricultural Areas: Soil Fertility and Crop Yieldmentioning
confidence: 98%
See 2 more Smart Citations
“…These measures prevent or delay nutrients accumulation in soil and its losses, whether through volatilization (NH 3 ), percolation, or runoff. The absence of measures and monitoring of applications can compromise the quality of water resources present in the swine units, as observed by the studies by Cadoná et al [23] and Loss et al [41]. In the first study, these authors observed in the supply wells of four swine units located in Braço do Norte, SC, an increase in N and P concentrations of in the water.…”
Section: Use Of Swine Manure In Agricultural Areas: Soil Fertility and Crop Yieldmentioning
confidence: 98%
“…However, in these conditions with high SM application the fertilizer efficiency index is reduced, promoting greater addition of nutrients in the soil, but with less use by the crops [26]. Consequently, there is a greater accumulation of nutrients in the soil and greater potential for soil pollution and surface and subsurface water resources through losses from runoff and leaching, respectively [5,23,[38][39][40][41][42]. In terms of runoff losses, the volume of the runoff and the amount of nutrients added to the soil (high doses of manure) are mainly responsible for the increase in losses.…”
Section: Use Of Swine Manure In Agricultural Areas: Soil Fertility and Crop Yieldmentioning
confidence: 99%
See 1 more Smart Citation